Augmentative therapies do not potentiate the antidepressant-like effects of deep brain stimulation in rats - Laver, Bryce (J Affect Disord, 2014)
BACKGROUND: Clinical trials have shown promising results with the use of subcallosal cingulate gyrus deep brain stimulation (DBS) for treatment-resistant depression. However, strategies to manage patients who do not respond to this therapy have not been explored in detail. In rats, DBS in the ventromedial prefrontal cortex (vmPFC) induces a significant antidepressant-like response in the forced swim test (FST). We have used this test to investigate potential interactions between DBS and clinically used augmentative regimens. METHODS: Rats undergoing the FST were treated with vmPFC DBS along with different augmentative drugs, namely buspirone, risperidone and pindolol. Locomotor activity was tested in an open field. RESULTS: DBS induced a significant reduction in immobility scores as compared to saline treated controls. These antidepressant-like effects, however, were not potentiated by the co-administration of buspirone, risperidone or pindolol. LIMITATIONS: Despite having good predictive validity, animal models are limited from a translational perspective. CONCLUSIONS: Our results indicate that that the antidepressant-like effects of vmPFC DBS in the FST are not enhanced by augmentative therapies.